Islamic Education According to Prof. Dr. Nur Ahmad Fadhil Lubis, MA. - Muhammad Habibi Azimi; Usiono Usiono; Azizah Hanum OK (Universitas Muhammadiyah Enrekang, 2024)
In this era, there is starting to be a lot of critical thinking from scientists and researchers regarding Islamic education. However, there is a professor in the field of philosophy in Indonesia who has studied studies related to Islamic to Western (American) studies, namely Prof. Dr. Nur Ahmad Fadhil Lubis, MA. Therefore, this scientific study aims to examine in more depth the thoughts on Islamic education from the perspective of Prof. Dr. Nur Ahmad Fadhil Lubis, MA. This scientific study uses the Systematic Literature Review (SLR) method with PRISMA analysis. The results of the analysis state that in his perspective, Prof. Fadhil Lubis views Islamic education as a very complex thing. Islamic education is not only an effort to form individuals with Islamic character but also a basis for building rahmatan lil ‘alamin and upholding baldattayyibahwarabbghafur (a prosperous country under the grace of Allah SWT). This is because Islamic education is a right that must be given to every individual, both men and women. Where this is in line with the word of Allah SWT in QS. At-Taubah verse 122, where Islamic education has 5 main objectives (maqasid al-shari’ah), namely protecting life, faith, reason, offspring and property.